Sirtuins and the circadian clock interplay in cardioprotection: focus on sirtuin 1 - Soni, Sanjeev Kumar (2021)
Fil: Soni, Sanjeev Kumar. Banaras Hindu University. Institute of Sciences. Department of Zoology. Chronobiology Laboratory; India